New Treatment Option for Clinical and Subclinical Mastitis in Dairy Cows Using Acoustic Pulse Technology (APT) - Gabriel Leitner; Eduard Papirov; Dan Gilad; Doron Haran; Oded Arkin; Alon Zuckerman; Yaniv Lavon (Dairy, 2021)
The effect of acoustic pulse technology (APT) on recovery, culling, milk yield, and economic benefits for 118 cows with subclinical mastitis was compared with a no-treatment control (59 vs. 59), and another 118 APT-treated cows with clinical mastitis were compared with antibiotic-treated controls (59 vs. 59). Recovery was defined as a decrease in somatic cell count (SCC) to <250 × 103 cells/mL in at least two out of three monthly milk recordings after treatments. For the subclinically infected cows, APT treatment resulted in 65.5% recovery, 0% culling, and additional milk yield of 2.74 L/cow per day compared to 35.6% recovery and 5.1% culling in the no-treatment controls. For the clinically infected cows, APT treatment resulted in 67.8% recovery, 6.8% culling, and additional milk yield of 3.9 L/cow per day compared to 35.6% recovery and 32.2% culling in the antibiotic-treated group. Bacteriological analysis was run for 95 (80%) cows with clinical mastitis (APT-46; AB-49). For cows with Escherichia coli infection, 85.7% (18/21) treated with APT recovered vs. 17.6% (3/17) in the antibiotic-treated group; for cows with streptococcal infection, 66.0% (12/18) in the APT-treated group recovered vs. 44.4% (8/18) in the antibiotic-treated group.